Quantifying the symmetry preferences of intermolecular interactions in organic crystal structures1. Issue 13 (7th April 2015) - Taylor, Robin; Allen, Frank H.; Cole, Jason C.
<x xml:space="preserve">Abstract</x> Many intermolecular interactions show preferences for particular crystallographic symmetries and the extent to which this is the case is quantifiable.